Pengaruh Kecerdasan Emosional, Dukungan Sosial, dan Work-Family Conflict Terhadap Stres Kerja Guru (Studi Kasus di SMAN 1 Cirebon) - Yulianti, Welly; Yaniawati, R. Poppy; Veranita, Mira (Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of emotional intelligence, social support, and work-family conflict on teacher work stress. The research method uses mixed methods with concurrent triangulation design, this study integrates qualitative and quantitative analysis which then the results are linked to each other. The population is 77 people, with a sample of 36 married female teachers at SMAN 1 Cirebon. Data collection through questionnaires, interviews, observations, and literature studies. Data analysis uses path analysis and test results with t-test. The results of the study indicate that emotional intelligence, social support, and work-family conflict have a significant influence on work stress in married female teachers at SMAN 1 Cirebon. However, partially only the work-family conflict variable has a positive and significant influence on work stress in married female teachers at SMAN 1 Cirebon.